Personalized and participatory medicine as a future tool to combat cardiovascular disease in developing countries - (:unkn) unknown (Bentham Science Publishers B.V., 2015)
Cardiovascular disease is one of the main leading causes of mortality. Approximately, 80% of cardiovascular deaths occur in low- and middle-income countries (LMICs). Current guidelines which are based on randomized controlled trials direct the cardiovascular diagnosis and treatment. Yet, such guidelines do not benefit every patient. Recent studies question the ‘one size fits all’ principle particularly in complex traits such as thrombosis. The cost and duration of genetic testing continue to decline rapidly and novel strategies are on the rise to determine individual susceptibility to diseases and responses to therapy. Multidimensional evaluation of the patient with his/her environment, genomics, detailed medical history, and compliance to treatment are crucial in preventing complications from antithrombotic treatment. In this review, we discuss some of the pharmacogenomic features of antithrombotic medications that are currently used. We believe current personalized medicine and pharmacogenomics are pivotal in elucidating contradictory results of randomized controlled trials to test the same antithrombotic regimen on all participants. © 2014 Bentham Science Publishers.
Keywords: Antiplatelet; Antithrombotic theraphy; Aspirin; Cardiovascular therapeutics; Clopidogrel; Personalized medicine; Pharmacogenomics